Trends of underweight, overweight, and obesity in Brazilian children and adolescents - Larissa S. Flores; Anelise R. Gaya; Ricardo D.S. Petersen; Adroaldo Gaya (Elsevier, 2013)
Objective: To describe and analyze the trends of occurrence of underweight, overweight, and obesity in schoolchildren. Methods: This was a longitudinal study of trends conducted in a voluntary sample of Brazilian children and adolescents. The sample was grouped by year of collection (period I: 2005 and 2006; period II: 2007 and 2008, and period III: 2009-2011), age category (children: 7 to 10 years, and adolescents: 11 to 14 years), and stratified by gender. The body mass index was used to classify the nutritional profile. Trend analysis was verified using multinomial logistic regression (p < 0.05). Results: Mean occurrences were 2.11% for underweight, 22.27% for overweight, and 6.8% for obesity. There was a decrease of underweight in male adolescents from period I to II, as well as an increase in female children from period II to III. Regarding overweight, there was an increase followed by a decrease in male children. Regarding obesity, there was an increase from period I to II in all age groups and for both genders. Conclusion: The prevalence of underweight was less than 5% in all categories of age and gender. However, the categories of overweight and obesity showed higher values, and together comprised almost 30% of the young Brazilian population; moreover, a trend toward increase in prevalence of obesity was observed up to the year 2008, followed by the maintenance of these high prevalence rates. Resumo: Objetivo: Descrever e analisar a tendência da ocorrência do baixo peso, sobrepeso e obesidade de escolares. Métodos: Estudo longitudinal de tendência realizado em uma amostra voluntária de crianças e adolescentes brasileiros. A amostra foi agrupada em ano de coleta (Período I: 2005 e 2006; Período II: 2007 e 2008; e Período III: 2009 a 2011), categoria de idade (crianças: sete a 10 anos, e adolescentes: 11 a 14 anos), e estratificada por sexo. O índice de massa corporal foi utilizado para classificar o perfil nutricional. A análise da tendência foi verificada através da Regressão Logística Multinomial (p < 0,05). Resultados: As médias de ocorrências foram de 2,11% no baixo peso, 22,27% no sobrepeso e 6,8% na obesidade. Identificou-se chance do baixo peso diminuir do período I para o II nos adolescentes do sexo masculino, e de aumentar nas crianças do sexo feminino do período II para o III. No sobrepeso, encontramos chance de aumento seguida de diminuição nas crianças do sexo masculino. Na obesidade, em todas as categorias de idade e em ambos os sexos, houve chance de aumento do período I para o II. Conclusão: A prevalência do baixo peso apresenta valores menores que 5% em todas as categorias de idade e sexo. No entanto, na categoria do sobrepeso e da obesidade, encontramos ocorrências mais elevadas, atingindo, juntas, quase 30% da população infanto-juvenil brasileira; além disso, evidenciamos uma chance de aumento na prevalência da obesidade até o ano de 2008 e, após, uma manutenção destas altas prevalências. Keywords: BMI, Malnutrition, Overweight, Obesity, Children and adolescents, Palavras-chave: IMC, Desnutrição, Sobrepeso, Obesidade, Crianças e adolescentes